Repair and maintenance works for low cost housing : issues and solution to promote sustainable housing concept / Yuhainis Abdul Talib, Amirul Helmi Abdul Malik and Siti Norsazlina Haron - Yuhainis, Abdul Talib; Amirul Helmi, Abdul Malik; Siti Norsazlina, Haron (2015)
Dwellings are a basic necessity to mankind for the purpose of security, comfort or to display a certain image, prestige or status. The aim of this study is to investigate and identify the repair and maintenance works for low cost flats. The objectives of this research is to identify the factors that most effect the building elements deterioration and to rank the building, mechanical and electrical elements that effect on the deterioration of the building. To achieve these objectives a survey is carried out based on structural questionnaires as well as physical observation by taking photograph of the building elements in the flats. The questionnaires survey conducted is presented using quantitative method (SPSS). The result show that there is growing demand for flats occupants. Based on the objective highlighted, the hypothesis created is tenants can prevent and slow down the building elements deterioration process with the make use of the factors provided. It was concluded that repairs and maintenance works should be done in good manner to satisfy tenants’ wants and also reduce the building elements deterioration.